Поняття конституційної правосуб’єктності - Кравчук, В.; Kravchuk, V. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2013)
У статті узагальнено основні наукові підходи до розуміння категорії «конституційна правосуб’єктність», проаналізовано їх вплив на визначення дефініції «конституційна правосуб’єктність». Ураховуючи взаємозв’язок конституційної правосуб’єктності із загальною теорією права, автор обґрунтовує власне визначення категорії «конституційна правосуб’єктність». The paper summarizes the main scientific approaches to understanding the category «constitutional legal personality» as well as analyzes these approaches’ impact on the definition of the term «constitutional legal personality». The constitutional legal personality in its whole can be ruled and recognized by the constitutional law. Therefore, it seems impossible to identify the categories «constitutional legal personality» and «constitutional-legal status». Moreover constitutional legal personality is an integral part of constitutional and legal status. Taking into consideration the ties between the constitutional legal personality and the general theory of law, as well as the law of other branches, the author gives own definition of the category «constitutional legal personality». The given theoretical suggestions can be applied in the educational process as well as serve as the subject of more detailed study.
The Concept of Constitutional Legal Personality
Keywords: конституційна правосуб’єктність; правосуб’єктність; суб’єкти конституційно-правових відносин; constitutional legal personality; personality; subjects of constitutional and legal relations